Designing a Novel Prototype to Assist and Monitor the Physically Handicapped People Using Intel Atom Processor - Kareem, Abdul; M., Vardhana; Kumar, Praveen (Recent Patents on Computer Science, 2016)
Background: It is very difficult for a physically handicapped people to lead their life as they are completely dependent on others for their needs. So it is essential to provide aid for the physically handicapped people to lead their life normally. Aim of our paper is to provide an assistant to physically disabled. Methods: Existing systems and patents to aid physically disabled is studied and latest trends are studied and proposed system is developed. Results: The prototype of the proposed system is developed using aurdino and different sensors are interfaced with the controller and tested with a patient. The system responded properly in fulfilling his basic needs. Conclusion: A novel prototype is designed and implemented using Aurdino microcontroller. This prototype helps to monitor and assist the physically disabled people. It helps the physically challenged people to lead their life in a very comfortable way. The basic requirements of the patients are fulfilled by the basic head movements and thus the physical condition of the patient is monitored. The proposed prototype is very helpful to the physically handicapped in fulfilling their needs. The proposed prototype is implemented and tested using Aurdino.
Keywords: APR-9600